Preparation of high-porosity Al2O3 ceramic foams via selective laser sintering of Al2O3 poly-hollow microspheres. Issue 4 (March 2020) - Liu, Shan-Shan; Li, Meng; Wu, Jia-Min; Chen, An-Nan; Shi, Yu-Sheng; Li, Chen-Hui
Abstract: In this paper, high-porosity Al2 O3 ceramic foams called Al2 O3 PHM ceramics were fabricated through selective laser sintering (SLS) via Al2 O3 poly-hollow microspheres (Al2 O3 PHMs). SLS parameters were optimized by an orthogonal experiment as to be laser power = 6 W, scanning speed = 1800 mm/s, and scanning space = 0.15 mm. The effect of sintering temperature on microstructure, shrinkage, porosity, phase composition, mechanical properties and pore size distribution of Al2 O3 PHM ceramics were investigated. When sintering temperature increased, Al2 O3 PHM ceramics contained only Al2 O3 phase and were gradually densified. With the raise of sintering temperature, the porosity of Al2 O3 PHM ceramics decreased gradually from 77.09% to 72.41%, but shrinkage in H direction and compressive strength of Al2 O3 PHM ceramics increased from 6.63% and 0.18 MPa to 13.10% and 0.72 MPa, respectively. Sintering temperature had little effect on pore size distribution of Al2 O3 PHM ceramics, which only declined from 24.2 to 21.4 μm with the increase of sintering temperature from 1600 to 1650 °C. This method can not only directly prepare ceramic foams with complex shapes, but also control properties of ceramic foams. It provides a simple preparation method for many kinds of ceramic foams with complex structure and high porosity by using PHMs with different composition.